Dampak Model Pembelajaran Contextual Teaching and Learning Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Pada Materi Segiempat - Gledisya Polontalo; Resmawan Resmawan; Siti Zakiyah; Abdul Wahab Abdullah (Jambura Journal of Mathematics Education, 2023)
This research aims to determine the differences in students mathematic concept understanding abilities between Contextual Teaching and Learning (CTL) model class and conventional model class on the topic of quadrilaterals. This research takes place in MTs Al-Khairaat Paguyaman and implementation time in even semester of the 2021/2022. This type of research is experimented with using pretest-posttest control group design. The population selected was all students of class VII MTs Al-Khairaat Paguyaman, as many as 47 people. Simple random sampling was chosen for the sampling technique and the sample members in this research amounted to 34 people divided into two classes with each class totaling 17 people. The data were collected using a test intsrument for understanding mathemacal concept. The results showed that the ability to understand mathematical concepts of students in the class that used the Contextual Teaching and Learning (CTL) model was higher than the class that used the conventional model of a quadrilateral.